2011
DOI: 10.1016/j.epsl.2010.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and chemical variability of fluvial sediments 2. Suspended-load silt (Ganga–Brahmaputra, Bangladesh)

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
206
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 329 publications
(222 citation statements)
references
References 81 publications
11
206
2
3
Order By: Relevance
“…These different end-members may be induced by mineralogical sorting of different minerals 328 bearing Na such as albite (Garzanti et al, 2010;2011) The isotopic composition of carbonates is shown in Figure 10 and is in agreement with 419 published data for bedload samples from the Ganga basin (Galy et al, 1999 Chambal sediment contribution to the Ganga sediment load also highlights that even in these 553 large systems, the transfer of suspended sediments can be rapid and vary on an annual basis. 554…”
Section: Introduction 26 27supporting
confidence: 77%
See 2 more Smart Citations
“…These different end-members may be induced by mineralogical sorting of different minerals 328 bearing Na such as albite (Garzanti et al, 2010;2011) The isotopic composition of carbonates is shown in Figure 10 and is in agreement with 419 published data for bedload samples from the Ganga basin (Galy et al, 1999 Chambal sediment contribution to the Ganga sediment load also highlights that even in these 553 large systems, the transfer of suspended sediments can be rapid and vary on an annual basis. 554…”
Section: Introduction 26 27supporting
confidence: 77%
“…Albite being the main Nacarrier in Ganga sediments (Garzanti et al, 2011), the release of Na is mainly attributed to its 692 weathering into kaolinite or smectite. …”
Section: Possible Weathering Mechanisms 687 688mentioning
confidence: 99%
See 1 more Smart Citation
“…These very similar constants show that the behaviour of Himalayan sediments with respect to the cation exchange composition is very similar to the sediments transported by the Amazon. These similarities most probably stem from the first-order resemblance of the mineralogical composition of both rivers (Garzanti et al, 2011;Martinelli et al, 1993).…”
Section: Nature Of Adsorbed Cationsmentioning
confidence: 98%
“…It should nevertheless be kept in mind that our estimates are formulated based on the Himalayan system at present. On longer timescales, the variability in both sediment (Goodbred and Kuehl, 2000) and weathering fluxes (Lupker et al, 2013) means that the relative importance of cation exchange fluxes in the global weathering budget has likely varied and hence should be treated carefully. Finally, it is worth mentioning that these estimates of weathering impact on the carbon cycle do not take into account the role of chemical weathering through sulfuric acid (Galy and France-Lanord, 1999;Turchyn et al, 2013) that is known to also contribute to the weathering budget of Himalayan erosion and does counteract long-term carbon sequestration (Calmels et al, 2007).…”
Section: Effect Of Cation Exchange On the Long-term Carbon Budget Of mentioning
confidence: 99%